2021
DOI: 10.3389/fpsyg.2021.565610
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Childhood Abuse and COVID-19 Hyperarousal in Adulthood: The Role of Social Environment

Abstract: BackgroundChildhood abuse increases risk for high levels of distress in response to future stressors. Interpersonal social support is protective for health, particularly during stress, and may be particularly beneficial for individuals who experienced childhood abuse.ObjectiveInvestigate whether childhood abuse predicts levels of posttraumatic stress disorder (PTSD) symptoms related to the COVID-19 pandemic, and test whether the perceived availability of social companionship preceding the pandemic moderates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 65 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…Several mechanisms may link prepandemic trauma histories and worse mental health, poorer sleep, and increased conflict during the COVID‐19 pandemic. Adults with trauma histories have been shown to report more PTSD‐related symptoms during the pandemic (John‐Henderson et al., 2021 ; Lahav, 2020 ; Seitz et al., 2021 ), and these symptoms have been related to poor sleep (Riemann et al., 2010 ) and interpersonal functioning (Markowitz et al., 2009 ). Social isolation has been related to depression, anxiety, and PTSD symptoms during the pandemic (Gonzalez‐Sanguino et al., 2020 ; Kaya et al., 2021 ), particularly among adults with trauma histories (John‐Henderson et al., 2021 ; Raj et al., 2020 ; Seitz et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several mechanisms may link prepandemic trauma histories and worse mental health, poorer sleep, and increased conflict during the COVID‐19 pandemic. Adults with trauma histories have been shown to report more PTSD‐related symptoms during the pandemic (John‐Henderson et al., 2021 ; Lahav, 2020 ; Seitz et al., 2021 ), and these symptoms have been related to poor sleep (Riemann et al., 2010 ) and interpersonal functioning (Markowitz et al., 2009 ). Social isolation has been related to depression, anxiety, and PTSD symptoms during the pandemic (Gonzalez‐Sanguino et al., 2020 ; Kaya et al., 2021 ), particularly among adults with trauma histories (John‐Henderson et al., 2021 ; Raj et al., 2020 ; Seitz et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adults with trauma histories have been shown to report more PTSD‐related symptoms during the pandemic (John‐Henderson et al., 2021 ; Lahav, 2020 ; Seitz et al., 2021 ), and these symptoms have been related to poor sleep (Riemann et al., 2010 ) and interpersonal functioning (Markowitz et al., 2009 ). Social isolation has been related to depression, anxiety, and PTSD symptoms during the pandemic (Gonzalez‐Sanguino et al., 2020 ; Kaya et al., 2021 ), particularly among adults with trauma histories (John‐Henderson et al., 2021 ; Raj et al., 2020 ; Seitz et al., 2021 ). Finally, data suggest sleep habits have worsened for many adults during the pandemic (Petrov et al., 2021 ), consistent with reports of sleep problems in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the variance associated with autonomic reactivity was removed, the direct effects of adversity history on mental health consequences of the pandemic were greatly attenuated. Other findings from cross-sectional (e.g., Kalia et al 2020) and longitudinal studies (John-Henderson et al 2021;Shreffler et al 2021) in the U.S. have reported the important impact of adversity on reactions to the pandemic. For example, Kalia et al (2020) found a significant indirect effect of childhood maltreatment on state anxiety via perceived threat of COVID-19, which included perceived risk of contracting the virus and the overall impact and severity of the pandemic.…”
Section: The Covid-19 Pandemic As a Stressormentioning
confidence: 97%